Wizja Unii Europejskiej w koncepcjach Prawa i Sprawiedliwości w świetle teorii międzyrządowych i ponadnarodowych - Staszczyk, Artur (Polityka i Społeczeństwo, 2020)
The paper explores the issue of the application of selected theories of European integration (intergovernmental and supranational) to explain the position of the Polish Justice Law and Justice party with regard to the functioning and future of the EU. The party, led by Jaroslaw Kaczynski, is a political formation which is actively engaged in the debate on the shape of the EU, pertaining to both its theoretical and practical policies. The ongoing debate has taken the form of battle between neo-functionalism and state-centric intergovernmental approach. The author believes that the main theory that explains the Law and Justice party’s approach to European issues is inter-governmentalism which aligns well with the concept of “Europe of Motherlands” adopted by the party. It proclaims the primacy of nation state and its interests in the process of European integration. This is tantamount to refuting the view that the EU can develop only in accordance with the neo-functionalism’s spill-over logic which will eventually lead to the formation of a European federation.